Reasons for no-show to referrals at a university eye clinic after eye examination via a mobile ophthalmic unit in a Brazilian region - Rezende, Marcelo Abrão [UNESP]; Hashimoto, Mitsuo [UNESP]; Padovani, Carlos Roberto [UNESP]; Schellini, Silvana Artioli [UNESP] (GN1 Sistemas e Publicacoes, 2021)
Purpose: This study aimed to identify patient’s reason for no-show at a university eye clinic after ophthalmic examination via a mobile ophthalmic unit, which provides comprehensive ophthalmic care to underserved communities in a region of Brazil. Methods: In 2017/2018, this prospective observational study searched for no-shows at referrals to a university eye clinic after an outreach program screening via a mobile ophthalmic unit in 10 municipalities in the central-western region of São Paulo, Brazil. A total of 1,928 patients underwent a comprehensive eye examination at no cost, and 37.1% of them needed referral to a university eye clinic for specialized examinations or surgeries. We used the following two main tools: (1) comparative analysis between patients who attended the referral and those who did not; (2) active search using a questionnaire to assess reasons for no-show. Results: Attendance to referrals was not influenced by age, gender, distance from the university hospital, number of ophthalmologists in the municipality, average family income, and visual acuity. The main cause for referrals was cataract (350 cases). No-show was most common among glaucoma/ suspected glaucoma (54.1%) cases, followed by strabismus (45%) and anterior segment disease (33.6%) cases. Many patients who did not attend the referral sought another service. Conclusion: Patient’s issues and lack of knowledge regarding their ophthalmic condition are the main reasons for no-show at referrals for free ophthalmic care. Thus, educational campaigns are needed to achieve consistently high attendance to prevent avoidable blindness.
Razão de não comparecimento à clínica oftalmológica da universidade após triagem em uma unidade móvel oftalmológica em uma região brasileira
Keywords: eye health services; Health promotion; health services accessibility; mobile health units; Patient dropouts